Cooling liquid suitable for new energy automobile and preparation method

By using aluminum nitride particles with an oxide layer and phase change microcapsules with hydroxyl-based double-terminated polydimethylsiloxane coatings in the coolant of new energy vehicles, the problems of low thermal conductivity and poor stability of the coolant have been solved, achieving efficient battery temperature control and improved stability.

CN120865854APending Publication Date: 2025-10-31FOSHAN DELIAN AUTOMOTIVE ACCESSORIES CO LTD

Patent Information

Application Number
CN202510942768.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-09
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

Existing coolants for new energy vehicles have low thermal conductivity. The process of adding phase change microcapsules and nanoparticles to coolants is complex, making it difficult to quickly store and release heat, and they also have poor stability.

Method used

Aluminum nitride particles with an oxide layer are used as thermally conductive particles, which are attached to the surface of phase change microcapsules or suspended in the base liquid. The phase change microcapsules are combined with hydroxyl-terminated polydimethylsiloxane-encapsulated layers, and the pH value is adjusted to 7.5-9.5 to optimize the composition of the base liquid and improve thermal conductivity and stability.

Benefits of technology

It significantly improves the thermal conductivity and heat exchange capacity of the coolant, ensuring battery temperature uniformity and stability, and is suitable for cooling systems in new energy vehicles.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of automobile cooling liquid, in particular to cooling liquid suitable for a new energy automobile and a preparation method. The cooling liquid suitable for the new energy automobile is prepared from the following components in parts by mass: 100 parts of base liquid, 2-4 parts of phase change microcapsules and 1-2 parts of heat conduction particles, a coating layer of the phase-change microcapsule is hydroxyalkyl double-terminated polydimethylsiloxane, the heat-conducting particles are aluminum nitride particles with oxide layers, the heat-conducting particles are divided into attached particles and free particles, the attached particles are attached to the surface of the phase-change microcapsule, and the free particles are suspended in the base liquid; the pH value of the cooling liquid is 7.5 to 9.5. The heat-conducting particles are aluminum nitride particles with oxide layers and are good in stability and insulativity, aluminum nitride has an extremely high heat conductivity coefficient, and the phase-change microcapsules and the heat-conducting particles cooperate with each other, so that the heat-conducting property of the cooling liquid is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of automotive coolant technology, and more particularly to a coolant suitable for new energy vehicles and its preparation method. Background Technology

[0002] Most new energy vehicle models use coolant flowing through cooling plates within the battery pack to remove heat through heat exchange. These cooling plates are typically metal pipes or plate structures, closely attached to the surface of the individual battery cells to achieve precise temperature control. This keeps the battery temperature within the optimal operating range of 25-40℃, while ensuring that the temperature difference between individual battery cells does not exceed 5℃ to avoid performance variations due to uneven temperature distribution. Existing technologies for new energy vehicle coolants employ phase change microcapsules to increase heat exchange capacity. For example, CN109810677A discloses a new energy vehicle coolant and its preparation method, where the core material of the phase change microcapsules is paraffin wax, and the wall material is polymethyl methacrylate, melamine resin, or polyethylene. However, these wall materials have very low thermal conductivity, making it difficult for phase change microcapsules to quickly store and release heat. New energy vehicle coolants also utilize nanoparticles to improve thermal conductivity. For example, CN 115584249A discloses a highly efficient thermally conductive new energy vehicle coolant and its preparation method, containing a suspension of silane-modified nano-alumina at a mass concentration of 1-5%. The nano-alumina accounts for only about 2% of the suspension, meaning it constitutes only about 0.2-1‰ of the entire coolant—a very small percentage. This only increases the coolant's thermal conductivity to 0.696 / (W / m·K). Furthermore, the nano-alumina is added to the system only after being prepared as a suspension, making the addition process relatively complex. Summary of the Invention

[0003] The purpose of this invention is to propose a coolant suitable for new energy vehicles and a preparation method thereof, the resulting coolant having good heat exchange performance and high thermal conductivity.

[0004] To achieve this objective, the present invention adopts the following technical solution:

[0005] A coolant suitable for new energy vehicles, comprising the following components by mass: 100 parts base liquid, 2-4 parts phase change microcapsules, and 1-2 parts thermally conductive particles;

[0006] The encapsulation layer of the phase change microcapsule is hydroxyl-based double-terminated polydimethylsiloxane, and the thermally conductive particles are aluminum nitride particles with an oxide layer. The thermally conductive particles are divided into attached particles and free particles. The attached particles are attached to the surface of the phase change microcapsule, and the free particles are suspended in the base liquid.

[0007] The pH value of the coolant is 7.5-9.5.

[0008] Furthermore, the thermally conductive particles are divided into attached particles and free particles, with the attached particles having a particle size of 50-100 nm and the free particles having a particle size of 1-5 μm.

[0009] Furthermore, the phase change microcapsules have a particle size of 10-50 μm and a coating layer thickness of 5-10 nm.

[0010] Furthermore, the base liquid is composed of ethylene glycol, propylene glycol, deionized water and diethylene glycol in a volume ratio of (40-50):(10-20):(30-40):(5-10).

[0011] Furthermore, by weight, the coolant also includes the following components: 1-2 parts triethanolamine, 0.3-0.5 parts polyvinylpyrrolidone, 0.5-0.8 parts triethanolamine sebacate, and 0.2-0.3 parts poly(N-isopropylacrylamide).

[0012] Furthermore, by weight, the coolant also includes the following components: 0.1-0.2 parts thickener and 0.05-0.1 parts defoamer.

[0013] A method for preparing a coolant suitable for new energy vehicles, the method comprising the following steps:

[0014] (1) Prepare phase change microcapsules with hydroxyl-based double-terminated polydimethylsiloxane as the encapsulation layer and paraffin as the phase change material;

[0015] (2) Disperse 2 to 4 parts of phase change microcapsules in 10 parts of base liquid by mass, and then add the attached particles treated with coupling agent and mix to obtain a mixture;

[0016] (3) Disperse the free particles in 90 parts of base liquid, then add the mixture and stir evenly;

[0017] (4) Adjust the pH of the coolant to 7.5-9.5.

[0018] Furthermore, in step (1):

[0019] After heating the paraffin wax until it melts, add an aqueous solution of sodium dodecylbenzenesulfonate and stir for 15-20 minutes to obtain a paraffin wax emulsion.

[0020] A coating layer solution was prepared by dissolving hydroxyalkyl-terminated polydimethylsiloxane with a viscosity greater than 5000 cp·25℃ in a volatile organic solvent.

[0021] The coating solution was added to the paraffin emulsion while the mixture was stirred at high speed. The reaction system was heated to 60-80°C and the reaction was carried out while stirring.

[0022] The generated phase change microcapsules were separated from the emulsion and dried at low temperature to obtain phase change microcapsules with a particle size of 10-50 μm and a coating thickness of 5-10 nm.

[0023] Further, in step (3), by weight, 1-2 parts of triethanolamine, 0.3-0.5 parts of polyvinylpyrrolidone, 0.5-0.8 parts of triethanolamine sebacate, 0.2-0.3 parts of poly(N-isopropylacrylamide), 0.1-0.2 parts of thickener and 0.05-0.1 parts of defoamer are added to 90 parts of base liquid, mixed evenly, and then the free particles are dispersed in the base liquid.

[0024] Furthermore, in step (2), 0.5-1 parts by weight of the attached particles of 50-100 nm are treated with a coupling agent;

[0025] Disperse 2-4 parts of phase change microcapsules in 10 parts of base liquid, then add the attached particles treated with coupling agent and mix to obtain a mixture.

[0026] The technical solution provided by this invention may include the following beneficial effects:

[0027] In this design, phase change microcapsules are coated with thermally conductive particles, which significantly increases the phase change rate of the microcapsule contents, thereby improving the heat transfer capacity of the coolant. Simultaneously, the free thermally conductive particles are distributed throughout the base fluid, enhancing the coolant's thermal conductivity. In particular, the thermally conductive particles in this design are aluminum nitride particles with an oxide layer, exhibiting good stability and insulation. Aluminum nitride possesses extremely high thermal conductivity; the synergistic effect of the phase change microcapsules and the thermally conductive particles greatly improves the coolant's thermal conductivity.

[0028] The base liquid obtained by blending ethylene glycol, propylene glycol, deionized water, and diethylene glycol in this solution has low viscosity, enabling it to flow rapidly in the cooling system, ensuring the circulation efficiency of the coolant and effectively transferring heat. This base liquid also has low electrical conductivity, making it suitable for new energy vehicles. Detailed Implementation

[0029] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the present invention.

[0030] A coolant suitable for new energy vehicles according to an embodiment of the present invention comprises the following components by mass: 100 parts base liquid, 2-4 parts phase change microcapsules, and 1-2 parts thermally conductive particles;

[0031] The encapsulation layer of the phase change microcapsule is hydroxyl-based double-terminated polydimethylsiloxane, and the thermally conductive particles are aluminum nitride particles with an oxide layer. The thermally conductive particles are divided into attached particles and free particles. The attached particles are attached to the surface of the phase change microcapsule, and the free particles are suspended in the base liquid.

[0032] The pH value of the coolant is 7.5-9.5.

[0033] In this design, phase change microcapsules are coated with thermally conductive particles, which significantly increases the phase change rate of the microcapsule contents, thereby improving the heat transfer capacity of the coolant. Simultaneously, the free thermally conductive particles are distributed throughout the base fluid, enhancing the coolant's thermal conductivity. In particular, the thermally conductive particles in this design are aluminum nitride particles with an oxide layer, exhibiting good stability and insulation. Aluminum nitride possesses extremely high thermal conductivity; the synergistic effect of the phase change microcapsules and the thermally conductive particles greatly improves the coolant's thermal conductivity.

[0034] This solution uses aluminum nitride particles with an oxide layer as heat-conducting particles, possessing both excellent thermal conductivity and good chemical stability. As an example, the aluminum nitride particles can be heated in an air atmosphere or oxygen-rich environment to form an aluminum oxide layer on their surface. The pH value of the coolant is limited to 7.5-9.5 to further ensure the stability of the oxide particles and the compatibility of the coolant with automotive components.

[0035] Furthermore, using hydroxyalkyl-terminated polydimethylsiloxane as the encapsulation layer of the phase change microcapsules provides excellent low-temperature flexibility. It does not easily harden or become brittle at low temperatures, maintaining the integrity of the microcapsule shell. Its molecular structure also imparts a degree of hydrophobicity, preventing moisture from entering the microcapsule interior, thus ensuring good stability in aqueous systems. This design preferably uses hydroxyalkyl-terminated polydimethylsiloxane with a viscosity greater than 5000 cp·25℃ to further enhance the stability of the phase change microcapsules.

[0036] Furthermore, the thermally conductive particles are divided into attached particles and free particles. The attached particles have a particle size of 50-100 nm, and the free particles have a particle size of 1-5 μm. The nano-sized attached particles are more likely to bind to the phase change microcapsules and exhibit better bonding strength. The micron-sized free particles are easier to disperse uniformly in the coolant, reducing the difficulty of dispersing the thermally conductive particles.

[0037] Preferably, the phase change microcapsules have a particle size of 10-50 μm and a coating thickness of 5-10 nm. The phase change material of the phase change microcapsules is paraffin.

[0038] In one embodiment of the present invention, the base liquid is composed of ethylene glycol, propylene glycol, deionized water and diethylene glycol in a volume ratio of (40-50):(10-20):(30-40):(5-10).

[0039] In this formulation, ethylene glycol, propylene glycol, deionized water, and diethylene glycol are blended to achieve a base liquid with a freezing point ≤ -45℃, a boiling point ≥ 125℃, and a thermal conductivity of 0.6 W / (m·K). The viscosity of the blended base liquid is <2000 mPa·s at -30℃ and >0.3 mPa·s at 100℃. The base liquid's low viscosity allows for rapid flow within the cooling system, ensuring efficient coolant circulation and effective heat transfer. Its low electrical conductivity makes it suitable for new energy vehicles.

[0040] In one embodiment of the present invention, the coolant further includes, by weight, the following components: 1-2 parts of triethanolamine, 0.3-0.5 parts of polyvinylpyrrolidone, 0.5-0.8 parts of triethanolamine sebacate and 0.2-0.3 parts of poly(N-isopropylacrylamide).

[0041] Triethanolamine (TEA) is a low-temperature antifreeze fortifier that works by reacting with H+ in water. + This combination inhibits ice crystal formation, further lowering the freezing point. Polyvinylpyrrolidone (PVP) is used as an antifreeze; its long-chain structure adsorbs onto the surface of ice crystals, preventing ice crystal aggregation and ensuring the low-temperature fluidity of the coolant. Triethanolamine sebacate is used for high-temperature anti-boiling and anti-evaporation, and also helps improve the system's corrosion resistance. For example, triethanolamine sebacate is generated by reacting triethanolamine (TEA) with sebacate in a molar ratio of 1:1.5–2.

[0042] Poly(N-isopropylacrylamide) (PNIPAM) is in a hydrophilic state below 25°C (low viscosity, which is beneficial for cold start), while the hydrophobic segments fold above 35°C, increasing the viscosity by 15%, thus serving as a temperature-sensitive rheology modifier for coolants.

[0043] In one embodiment of the present invention, the coolant further includes, by weight, 0.1-0.2 parts of thickener and 0.05-0.1 parts of defoamer.

[0044] For example, in this embodiment of the invention, sodium carboxymethyl cellulose (CMC) is used as a thickener to improve the suspension stability of the microcapsules and prevent sedimentation from clogging the water pump or pipes; a silicone-based defoamer is also used. Corrosion inhibitors, such as benzotriazole, are also added to the coolant.

[0045] Accordingly, the present invention also provides a method for preparing a coolant suitable for new energy vehicles. This method, used to prepare the aforementioned coolant suitable for new energy vehicles, includes the following steps:

[0046] (1) Prepare phase change microcapsules with hydroxyl-based double-terminated polydimethylsiloxane as the encapsulation layer and paraffin as the phase change material;

[0047] (2) Disperse 2 to 4 parts of phase change microcapsules in 10 parts of base liquid by mass, and then add the attached particles treated with coupling agent and mix to obtain a mixture;

[0048] (3) Disperse the free particles in 90 parts of base liquid, then add the mixture and stir evenly;

[0049] (4) Adjust the pH of the coolant to 7.5-9.5.

[0050] The coolant prepared by the above method exhibits excellent thermal conductivity and heat transfer performance, and also demonstrates good stability. This method first utilizes the suspension effect of a small amount of base liquid to allow adhering particles to attach to the phase change microcapsules. Then, free particles are mixed into the base liquid, and finally, the phase change microcapsules are incorporated. This reduces the stirring time of the phase change microcapsules and prevents excessive stirring time from affecting the number of thermally conductive particles adhering to the surface of the microcapsules.

[0051] Furthermore, in step (1):

[0052] After heating the paraffin wax until it melts, add an aqueous solution of sodium dodecylbenzenesulfonate and stir for 15-20 minutes to obtain a paraffin wax emulsion.

[0053] A coating layer solution was prepared by dissolving hydroxyalkyl-terminated polydimethylsiloxane with a viscosity greater than 5000 cp·25℃ in a volatile organic solvent.

[0054] The coating solution was added to the paraffin emulsion while the mixture was stirred at high speed. The reaction system was heated to 60-80°C and the reaction was carried out while stirring.

[0055] The generated phase change microcapsules were separated from the emulsion and dried at low temperature to obtain phase change microcapsules with a particle size of 10-50 μm and a coating thickness of 5-10 nm.

[0056] A hydroxyalkyl-based double-terminated polydimethylsiloxane with a viscosity greater than 5000 cp·25℃ was selected as the encapsulation layer to form a stable encapsulation structure. Specifically, high-viscosity hydroxyalkyl-based double-terminated polydimethylsiloxane can be obtained by extending the polymerization time and adding chain extenders.

[0057] Preferably, in step (3), by weight, 1-2 parts of triethanolamine, 0.3-0.5 parts of polyvinylpyrrolidone, 0.5-0.8 parts of triethanolamine sebacate, 0.2-0.3 parts of poly(N-isopropylacrylamide), 0.1-0.2 parts of thickener and 0.05-0.1 parts of defoamer are added to 90 parts of base liquid, mixed evenly, and then the free particles are dispersed in the base liquid.

[0058] Preferably, in step (2), 0.5-1 parts by weight of the attached particles of 50-100 nm are treated with a coupling agent;

[0059] Disperse 2-4 parts of phase change microcapsules in 10 parts of base liquid, then add the attached particles treated with coupling agent and mix to obtain a mixture.

[0060] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods in the following embodiments that do not specify specific conditions are generally performed according to conventional methods and conditions or according to the product instructions. Unless otherwise specified, the reagents are commercially available; and the performance of products from different sources does not have a significant impact.

[0061] Example 1

[0062] This embodiment of a coolant suitable for new energy vehicles comprises, by weight, the following components: 100 parts base liquid, 2 parts phase change microcapsules, 1 part thermally conductive particles, 1 part triethanolamine, 0.3 parts polyvinylpyrrolidone, 0.5 parts triethanolamine sebacic acid salt, and 0.2 parts poly(N-isopropylacrylamide), 0.1 parts thickener, and 0.05 parts defoamer. The thermally conductive particles are aluminum nitride particles with an oxide layer. The base liquid is composed of ethylene glycol, propylene glycol, deionized water, and diethylene glycol in a volume ratio of 40:20:40:10.

[0063] The steps for preparing the coolant are as follows:

[0064] (1) After heating paraffin to melt, add sodium dodecylbenzenesulfonate aqueous solution and stir for 15 min to obtain paraffin emulsion; dissolve hydroxyalkyl double-terminated polydimethylsiloxane with a viscosity greater than 5000cp·25℃ in a volatile organic solvent to prepare a coating layer solution; add the coating layer solution to the paraffin emulsion and stir at high speed, raise the reaction system to 60℃ and carry out the reaction while maintaining stirring; separate the generated phase change microcapsules from the emulsion and dry them at low temperature to obtain phase change microcapsules with a particle size of 10-40μm and a coating layer thickness of 5-10nm.

[0065] (2) By mass, 2 parts of phase change microcapsules are dispersed in 10 parts of base liquid, and then 0.5 parts of attached particles with a particle size of 50-100nm treated with coupling agent are added and mixed to obtain a mixture;

[0066] (3) By weight, add 1 part of triethanolamine, 0.3 parts of polyvinylpyrrolidone, 0.5 parts of triethanolamine sebacate, 0.2 parts of poly(N-isopropylacrylamide), 0.1 parts of thickener and 0.05 parts of defoamer to 90 parts of base liquid respectively, then mix in 0.5 parts of free particles with a particle size of 1-5 μm, then add the mixture and stir evenly;

[0067] (4) Adjust the pH of the coolant to 7.5-9.5 with sodium hydroxide.

[0068] Example 2

[0069] This embodiment provides a coolant suitable for new energy vehicles, comprising the following components by weight: 100 parts base liquid, 3 parts phase change microcapsules, 2 parts thermally conductive particles, 2 parts triethanolamine, 0.3 parts polyvinylpyrrolidone, 0.5 parts triethanolamine sebacic acid salt, and 0.2 parts poly(N-isopropylacrylamide), 0.1 parts thickener, and 0.08 parts defoamer. The thermally conductive particles are aluminum nitride particles with an oxide layer. The base liquid is composed of ethylene glycol, propylene glycol, deionized water, and diethylene glycol in a volume ratio of 50:20:40:5.

[0070] The steps for preparing the coolant are as follows:

[0071] (1) After heating paraffin to melt, add sodium dodecylbenzenesulfonate aqueous solution and stir for 15 min to obtain paraffin emulsion; dissolve hydroxyalkyl double-terminated polydimethylsiloxane with a viscosity greater than 5000cp·25℃ in a volatile organic solvent to prepare a coating layer solution; add the coating layer solution to the paraffin emulsion and stir at high speed, raise the reaction system to 60℃ and carry out the reaction while maintaining stirring; separate the generated phase change microcapsules from the emulsion and dry them at low temperature to obtain phase change microcapsules with a particle size of 10-40μm and a coating layer thickness of 5-10nm.

[0072] (2) By mass, 3 parts of phase change microcapsules are dispersed in 10 parts of base liquid, and then 1 part of attached particles with a particle size of 50-100nm treated with coupling agent are added and mixed to obtain a mixture.

[0073] (3) By weight, add 2 parts of triethanolamine, 0.3 parts of polyvinylpyrrolidone, 0.5 parts of triethanolamine sebacate, 0.2 parts of poly(N-isopropylacrylamide), 0.1 parts of thickener and 0.08 parts of defoamer to 90 parts of base liquid respectively, then mix in 1 part of free particles with a particle size of 1-5 μm, then add the mixture and stir evenly;

[0074] (4) Adjust the pH of the coolant to 7.5-9.5 with sodium hydroxide.

[0075] Example 3

[0076] This embodiment of a coolant suitable for new energy vehicles comprises, by weight, the following components: 100 parts base liquid, 3 parts phase change microcapsules, 1.5 parts thermally conductive particles, 1 part triethanolamine, 0.4 parts polyvinylpyrrolidone, 0.6 parts triethanolamine sebacic acid salt, and 0.3 parts poly(N-isopropylacrylamide), 0.2 parts thickener, and 0.08 parts defoamer. The thermally conductive particles are aluminum nitride particles with an oxide layer. The base liquid is composed of ethylene glycol, propylene glycol, deionized water, and diethylene glycol in a volume ratio of 40:10:30:10.

[0077] The steps for preparing the coolant are as follows:

[0078] (1) After heating paraffin to melt, add sodium dodecylbenzenesulfonate aqueous solution and stir for 20 min to obtain paraffin emulsion; dissolve hydroxyalkyl double-terminated polydimethylsiloxane with a viscosity greater than 5000 cp·25℃ in a volatile organic solvent to prepare a coating layer solution; add the coating layer solution to the paraffin emulsion and stir at high speed, raise the reaction system to 60℃ and carry out the reaction while maintaining stirring; separate the generated phase change microcapsules from the emulsion and dry them at low temperature to obtain phase change microcapsules with a particle size of 20-50 μm and a coating layer thickness of 5-10 nm.

[0079] (2) By mass, 3 parts of phase change microcapsules are dispersed in 10 parts of base liquid, and then 1 part of attached particles with a particle size of 50-100nm treated with coupling agent are added and mixed to obtain a mixture.

[0080] (3) By weight, add 1 part of triethanolamine, 0.4 parts of polyvinylpyrrolidone, 0.6 parts of triethanolamine sebacate, 0.3 parts of poly(N-isopropylacrylamide), 0.2 parts of thickener and 0.08 parts of defoamer to 90 parts of base liquid, then mix in 0.5 parts of free particles with a particle size of 1-5 μm, then add the mixture and stir evenly;

[0081] (4) Adjust the pH of the coolant to 7.5-9.5 with sodium hydroxide.

[0082] Example 4

[0083] This embodiment of a coolant suitable for new energy vehicles comprises, by weight, the following components: 100 parts base liquid, 4 parts phase change microcapsules, 1.5 parts thermally conductive particles, 1 part triethanolamine, 0.4 parts polyvinylpyrrolidone, 0.6 parts triethanolamine sebacic acid salt, and 0.3 parts poly(N-isopropylacrylamide), 0.2 parts thickener, and 0.1 parts defoamer. The thermally conductive particles are aluminum nitride particles with an oxide layer. The base liquid is composed of ethylene glycol, propylene glycol, deionized water, and diethylene glycol in a volume ratio of 40:20:40:5.

[0084] The steps for preparing the coolant are as follows:

[0085] (1) After heating paraffin to melt, add sodium dodecylbenzenesulfonate aqueous solution and stir for 20 min to obtain paraffin emulsion; dissolve hydroxyalkyl double-terminated polydimethylsiloxane with a viscosity greater than 5000cp·25℃ in a volatile organic solvent to prepare a coating layer solution; add the coating layer solution to the paraffin emulsion and stir at high speed, raise the reaction system to 70℃ and carry out the reaction while maintaining stirring; separate the generated phase change microcapsules from the emulsion and dry them at low temperature to obtain phase change microcapsules with a particle size of 20-50μm and a coating layer thickness of 5-10nm.

[0086] (2) By mass, 4 parts of phase change microcapsules are dispersed in 10 parts of base liquid, and then 0.5 parts of attached particles with a particle size of 50-100nm treated with coupling agent are added and mixed to obtain a mixture.

[0087] (3) By weight, add 1 part of triethanolamine, 0.4 parts of polyvinylpyrrolidone, 0.6 parts of triethanolamine sebacate, 0.3 parts of poly(N-isopropylacrylamide), 0.2 parts of thickener and 0.1 parts of defoamer to 90 parts of base liquid respectively, then mix in 1 part of free particles with a particle size of 1-5 μm, then add the mixture and stir evenly;

[0088] (4) Adjust the pH of the coolant to 7.5-9.5 with sodium hydroxide.

[0089] Example 5

[0090] This embodiment of a coolant suitable for new energy vehicles comprises, by weight, the following components: 100 parts base liquid, 3 parts phase change microcapsules, 2 parts thermally conductive particles, 2 parts triethanolamine, 0.4 parts polyvinylpyrrolidone, 0.7 parts triethanolamine sebacic acid salt, and 0.3 parts poly(N-isopropylacrylamide), 0.2 parts thickener, and 0.1 parts defoamer. The thermally conductive particles are aluminum nitride particles with an oxide layer. The base liquid is composed of ethylene glycol, propylene glycol, deionized water, and diethylene glycol in a volume ratio of 40:10:40:10.

[0091] The steps for preparing the coolant are as follows:

[0092] (1) After heating paraffin to melt, add sodium dodecylbenzenesulfonate aqueous solution and stir for 20 min to obtain paraffin emulsion; dissolve hydroxyalkyl double-terminated polydimethylsiloxane with a viscosity greater than 5000 cp·25℃ in a volatile organic solvent to prepare a coating layer solution; add the coating layer solution to the paraffin emulsion and stir at high speed, raise the reaction system to 80℃ and carry out the reaction while maintaining stirring; separate the generated phase change microcapsules from the emulsion and dry them at low temperature to obtain phase change microcapsules with a particle size of 20-50 μm and a coating layer thickness of 5-10 nm.

[0093] (2) By mass, 3 parts of phase change microcapsules are dispersed in 10 parts of base liquid, and then 1 part of attached particles with a particle size of 50-100nm treated with coupling agent are added and mixed to obtain a mixture.

[0094] (3) By weight, add 2 parts of triethanolamine, 0.4 parts of polyvinylpyrrolidone, 0.7 parts of triethanolamine sebacate, 0.3 parts of poly(N-isopropylacrylamide), 0.2 parts of thickener and 0.1 parts of defoamer to 90 parts of base liquid respectively, then mix in 1 part of free particles with a particle size of 1-5 μm, then add the mixture and stir evenly;

[0095] (4) Adjust the pH of the coolant to 7.5-9.5 with sodium hydroxide.

[0096] Example 6

[0097] This embodiment of a coolant suitable for new energy vehicles comprises, by weight, the following components: 100 parts base liquid, 4 parts phase change microcapsules, 1.3 parts thermally conductive particles, 2 parts triethanolamine, 0.5 parts polyvinylpyrrolidone, 0.8 parts triethanolamine sebacic acid salt, and 0.3 parts poly(N-isopropylacrylamide), 0.2 parts thickener, and 0.1 parts defoamer. The thermally conductive particles are aluminum nitride particles with an oxide layer. The base liquid is composed of ethylene glycol, propylene glycol, deionized water, and diethylene glycol in a volume ratio of 50:20:30:10.

[0098] The steps for preparing the coolant are as follows:

[0099] (1) After heating paraffin to melt, add sodium dodecylbenzenesulfonate aqueous solution and stir for 20 min to obtain paraffin emulsion; dissolve hydroxyalkyl double-terminated polydimethylsiloxane with a viscosity greater than 5000 cp·25℃ in a volatile organic solvent to prepare a coating layer solution; add the coating layer solution to the paraffin emulsion and stir at high speed, raise the reaction system to 80℃ and carry out the reaction while maintaining stirring; separate the generated phase change microcapsules from the emulsion and dry them at low temperature to obtain phase change microcapsules with a particle size of 20-50 μm and a coating layer thickness of 5-10 nm.

[0100] (2) By mass, 4 parts of phase change microcapsules are dispersed in 10 parts of base liquid, and then 0.5 parts of attached particles with a particle size of 50-100nm treated with coupling agent are added and mixed to obtain a mixture.

[0101] (3) By weight, add 2 parts of triethanolamine, 0.4 parts of polyvinylpyrrolidone, 0.7 parts of triethanolamine sebacate, 0.3 parts of poly(N-isopropylacrylamide), 0.2 parts of thickener and 0.1 parts of defoamer to 90 parts of base liquid, then mix in 0.8 parts of free particles with a particle size of 1-5 μm, then add the mixture and stir evenly;

[0102] (4) Adjust the pH of the coolant to 7.5-9.5 with sodium hydroxide.

[0103] The coolants of Examples 1-6 were tested. Each coolant was left to stand at 80°C for 72 hours, and no stratification, flocculation, or viscosity abnormalities were observed (viscosity change should be <10%). The thermal conductivity of the coolants in each example was tested using the hot wire method and was within the range of 0.8-0.9 W / (m·K). Stability tests were performed on the coolants of Examples 1-6: after 50 thermal cycles (-20°C to 100°C), the latent heat decay rate of phase change was tested (<5%), and it was observed whether the heat-conducting particles settled or agglomerated, and whether the phase change microcapsules were damaged. Winter tests were conducted on the coolants of Examples 1-6. During a cold start at -30°C, the battery temperature rose from -25°C to 25°C in 13-16 minutes. Under high-temperature conditions, the motor controller temperature fluctuation was controlled within ±3°C, meeting the wide-temperature-range heat dissipation requirements.

[0104] Other components and operations of the coolant and its preparation method for new energy vehicles according to embodiments of the present invention are known to those skilled in the art and will not be described in detail here. When numerical ranges are given in the embodiments, it should be understood that, unless otherwise stated in the present invention, both endpoints of each numerical range and any value between the two endpoints may be selected. The performance described can be achieved within the proportions ranged in the present invention. Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly understood by those skilled in the art to which this invention pertains.

[0105] Although embodiments of the invention have been shown and described, those skilled in the art will understand that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the claims and their equivalents.

Claims

1. A coolant suitable for new energy vehicles, characterized in that, By mass, it includes the following components: 100 parts base liquid, 2-4 parts phase change microcapsules, and 1-2 parts thermally conductive particles; The encapsulation layer of the phase change microcapsule is hydroxyl-based double-terminated polydimethylsiloxane, and the thermally conductive particles are aluminum nitride particles with an oxide layer. The thermally conductive particles are divided into attached particles and free particles. The attached particles are attached to the surface of the phase change microcapsule, and the free particles are suspended in the base liquid. The pH value of the coolant is 7.5-9.

5.

2. The coolant according to claim 1, characterized in that, The thermally conductive particles are divided into attached particles and free particles. The attached particles have a particle size of 50-100 nm, and the free particles have a particle size of 1-5 μm.

3. The coolant according to claim 1, characterized in that, The phase change microcapsules have a particle size of 10-50 μm and a coating thickness of 5-10 nm.

4. The coolant according to claim 1, characterized in that, The base liquid is composed of ethylene glycol, propylene glycol, deionized water and diethylene glycol in a volume ratio of (40-50):(10-20):(30-40):(5-10).

5. The coolant according to claim 1, characterized in that, By weight, it also includes the following components: 1-2 parts triethanolamine, 0.3-0.5 parts polyvinylpyrrolidone, 0.5-0.8 parts triethanolamine sebacate and 0.2-0.3 parts poly(N-isopropylacrylamide).

6. The coolant according to claim 1, characterized in that, By weight, it also includes the following components: 0.1-0.2 parts thickener and 0.05-0.1 parts defoamer.

7. A method for preparing a coolant suitable for new energy vehicles, characterized in that, This method is used to prepare the coolant suitable for new energy vehicles according to any one of claims 1 to 6, and the method includes the following steps: (1) Prepare phase change microcapsules with hydroxyl-based double-terminated polydimethylsiloxane as the encapsulation layer and paraffin as the phase change material; (2) Disperse 2 to 4 parts of phase change microcapsules in 10 parts of base liquid by mass, and then add the attached particles treated with coupling agent and mix to obtain a mixture; (3) Disperse the free particles in 90 parts of base liquid, then add the mixture and stir evenly; (4) Adjust the pH of the coolant to 7.5-9.

5.

8. The preparation method according to claim 7, characterized in that, In step (1): After heating the paraffin wax until it melts, add an aqueous solution of sodium dodecylbenzenesulfonate and stir for 15-20 minutes to obtain a paraffin wax emulsion. A coating layer solution was prepared by dissolving hydroxyalkyl-terminated polydimethylsiloxane with a viscosity greater than 5000 cp·25℃ in a volatile organic solvent. The coating solution was added to the paraffin emulsion while the mixture was stirred at high speed. The reaction system was heated to 60-80°C and the reaction was carried out while stirring. The generated phase change microcapsules were separated from the emulsion and dried at low temperature to obtain phase change microcapsules with a particle size of 10-50 μm and a coating thickness of 5-10 nm.

9. The preparation method according to claim 7, characterized in that, In step (3), by weight, 1-2 parts of triethanolamine, 0.3-0.5 parts of polyvinylpyrrolidone, 0.5-0.8 parts of triethanolamine sebacate, 0.2-0.3 parts of poly(N-isopropylacrylamide), 0.1-0.2 parts of thickener and 0.05-0.1 parts of defoamer are added to 90 parts of base liquid, mixed evenly, and then the free particles are dispersed in the base liquid.

10. The preparation method according to claim 7, characterized in that, In step (2), 0.5-1 parts by weight of the attached particles of 50-100 nm are treated with a coupling agent. Disperse 2-4 parts of phase change microcapsules in 10 parts of base liquid, then add the attached particles treated with coupling agent and mix to obtain a mixture.

Citation Information

Patent Citations

  • Efficient heat-conducting new energy automobile cooling liquid and preparation method thereof

    CN115584249A

  • New energy vehicle cooling liquid and preparation method thereof

    CN109810677A

  • Low-oil cooling liquid

    CN112812756A

  • Phase change microcapsule suspension as well as preparation method and application thereof

    CN115678505A

  • Use of aqueous microcapsule dispersions as heat transfer liquids

    CN1774489A

Cited By

  • Cooling medium for charging cable liquid cooling heat dissipation system and preparation method

    CN121922430A